Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Keputusan Pembelian Penggunaan Jasa Laundry Pada CV. Aru Hi Prima Jasa Ciputat – Tangerang - Budi Sukisworo; Sugeng Widodo (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this research is to determine the influence of service quality and promotion on purchasing decisions to use laundry services at CV. Aru Hi Prima Ciputat-Tangerang Services. totaling 8,302 customers with a sampling technique using the Slovin formula with an error rate of 10%. So the number of samples obtained was 99 respondents. The research method used is a quantitative research method, with an associative approach. The analytical tests used in this research are validity tests, reliability tests, classical assumption tests, linear regression tests, correlation tests, determination tests, hypothesis tests using t (partial) and F tests (simultaneous) with the help of SPSS 20 for Windows software. Based on the results of the research conducted, it is known that the Service Quality variable (X1) is marked by the number of statements answered with the words strongly agree, 428 or 43.3%, the Promotion variable (X2) is marked by the number of statements answered with the words strongly agree, 270 or 270. 27.3%, and the decision to purchase laundry services was marked by the number of statements answered with the words strongly agree, 577 or 58.2% of the total score. The results of the research analysis show a positive and significant influence between service quality and promotion on purchasing decisions to use laundry services. This can be seen from the value of the coefficient of determination or simultaneous contribution of 29.1%, while the rest is influenced by other factors that were not carried out in this research. Hypothesis testing obtained a value of Fcount>Ftable or (19.728>4.83), this is also strengthened by a significance value of 0.000<0.01, so it can be concluded that Ho is rejected and H3 is accepted. This means that the variables of Service Quality and Promotion simultaneously have a positive and significant effect on the Purchase Decision to Use Laundry Services. Aru Hi Prima Ciputat-Tangerang Services.